2016
DOI: 10.1002/lary.25954
|View full text |Cite
|
Sign up to set email alerts
|

Isolated perifacial lymph node metastasis in oral squamous cell carcinoma with clinically node-negative neck

Abstract: 4 Laryngoscope, 126:2252-2256, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…With a random effects model, the pooled estimated cervical level IIb metastases rate was 6% (95% CI: 4.0–7.0). When the data in the largest weight 25 were removed, the result was 5% (95% CI: 4.0–6.0), and when the data in the minimum weight 38 were deleted, the result was 5% (95% CI: 4.0–7.0). With a fixed-effects model, the pooled estimated cervical IIb metastases rate for tongue SCC was 7% (95% CI: 5.0–10.0).…”
Section: Resultsmentioning
confidence: 99%
“…With a random effects model, the pooled estimated cervical level IIb metastases rate was 6% (95% CI: 4.0–7.0). When the data in the largest weight 25 were removed, the result was 5% (95% CI: 4.0–6.0), and when the data in the minimum weight 38 were deleted, the result was 5% (95% CI: 4.0–7.0). With a fixed-effects model, the pooled estimated cervical IIb metastases rate for tongue SCC was 7% (95% CI: 5.0–10.0).…”
Section: Resultsmentioning
confidence: 99%
“…However, some of the aforementioned articles suggest removing PFNs, especially in oral carcinomas and even in N0 cases if the cancer involves the tongue or buccal mucosa. 19 In the near future, more substantial studies will be needed to give definitive indications to PFN removal in relation to the primary cancer and the state of the neck. Nevertheless, this would not be possible without precise anatomic knowledge of the PFNs and an accurate description of a surgical technique that provides complete removal of these lymph nodes without damaging the MMN.…”
Section: Discussionmentioning
confidence: 99%
“…In a report by Lim et al [ 32 ], 41 patients with cN0 tongue SCC underwent 72 neck dissections, and positive perivascular lymph nodes occurred in four (5.6%) of the 72 procedures; 14 patients with cN0 SCC of the floor of the mouth underwent 27 neck dissections, and positive perivascular lymph nodes occurred in two (7.4%) of the 27 procedures. In another study published by Agarwal et al [ 33 ], the authors found that in 231 patients with cN0 oral SCC, the incidence of positive perivascular lymph nodes was 7.1% in tongue SCC and 7.8% in buccal SCC, and the difference was not significant. The perivascular lymph nodes in the abovementioned two studies referred to the prevascular lymph nodes and the retrovascular lymph nodes and were similar to the superior group of lymph nodes in the current study.…”
Section: Discussionmentioning
confidence: 95%